Respuestas

2013-04-20T21:33:06+02:00

-((2/5)-((3/8)-(2/4))).(5/2)-(6/3)/(3/6)

-((2/5)-((3/8-2/4))).(5/2)-(6/3)/(3/6)

-((2/5)-((-1/8)).(5/2)-(6/3)/(3/6)

-(2/5+1/8).(5/2)-(6/3)/(3/6)

-(21/40). (5/2)-(4)

 -21/40. -1 1/2

63/80

 

 

  • Usuario de Brainly
2013-04-20T21:47:31+02:00

-((2/5)-((3/8)-(2/4))).(5/2)-(6/3)/(3/6) =

 

-((2/5)-(- 1/8)).(5/2)-(4) = 

 

-(2/5 +  1/8).((5/2)-(8/2)) =

 

-(16/40 + 5/40).( - 3/2) =

 

-(23/40).( - 3/2) =

 

+ 69/80

 

espero que te sirva, salu2!!!!!